A Locking-Free Scheme of Nonconforming Rectangular Finite Element for the Planar Elasticity (Journal of Computational Mathematics, 2004)
In this paper, the authors present a locking-free scheme of the lowest order nonconforming rectangle finite element method for the planar elasticity with the pure displacement boundary condition. Optimal order error estimate, uniformly for the Lamé constant $λ\in(0,∞)$ is obtained.
Keywords: Locking-free; Planar elasticity; Nonconforming finite element method.